Archival processing of the Burgos family photograph collection - Deloria, Michelle R.; Obille, Kathleen Lourdes B.; Santos, Mark Anthony A.; Domingo Abella Collection . (Quezon City School of Library and Information Studies, University of the Philippines, Diliman, 2019)
The initial conception of the project in 2018 was assessed based on the socio-political and historical value of the Burgos family photograph collection. The Burgos family photograph collection included is the published and unpublished (black and white, and colored) photographs, from 1984 to 1995 (including undated photographs). Most of these photographs were published in their newspapers such as the Bicol Forum, People‘s Voice, Sunday, Ang Bagong Masa, Ang Pahayagang Malaya, Metropolitan Mail, Midday, Ang Tinig ng Masa, and the WE Forum. Some photographs were also published in other newspapers which the Burgos Family did not own such as, Ang Bayan Ko, Bicolandia, Ito ang Pilipinas, Monitor, Pare Ko, People‘s Tonite, Talarawan, and Taliba. The photographers originally owned the photographs that were used in other publications but were submitted to the WE Forum and Malaya. This project recognizes that the photographers were the original owners of the photographs as they submitted these to the WE Forum and Malaya. However, some were not labelled, hence even the Burgos Family could not ascertain the provenance of the photos.

The significance of the Burgos family collection is that part of the photograph collection‘s content during the reign of President Ferdinand E. Marcos, Sr. When martial law was proclaimed on 23 September 1972, the mass media was controlled and run by the Marcos government. Everything was censored. Anything that was deemed subversive was to be eradicated or exterminated. Many radio, television, and print media were closed. Despite the gruesome circumstances, opposition papers, alternative press, or the mosquito press spread across the nation. The mosquito press, according to Alviar (2013), ―refers to the anti-dictatorship newspapers during the Martial Law era‖ (para.6). One of the prominent article series which the WE Forum published was on the fake medals and false war claims of President Ferdinand E. Marcos, Sr. in 1982. It was because of this that angered President Marcos when he was asked about the subject during the Veteran‘s celebration. Holding the WE Forum newspaper in his hand, he remarked that he will let the publisher eat it. President Marcos coined the mosquito press referring to the WE Forum newspaper. Mosquitoes being small, bite and pester the Marcos administration.

The photographs are captured moments of truth, an evidence(s) of what has transpired. It is in this sense, that the photograph collection should be accessed by people to tell its story of the past and renew memories which embodies our identities entwined in history. It is by this material which can be a medium to show facts (that displays a scene, act, individual or group, an event, object, and so on) to dispute, correct, or simply show the truth of the matter of fact in any point in our history.

To facilitate preservation, access, and retrieval, the collection was organized. Specifically, an inventory/simple database was made to provide a general condition, count, and organization of the photograph collection. The processing of the photographs included basic preservation and conservation treatments such as dry cleaning, removing staple wires, interleaving the photographs with nonacidic paper, labelling and transferring to new containers (envelopes and archival boxes), alphabetically arranging labelled folders in the boxes, and encoding the labels in Microsoft office, as per description, preservation, and retrieval purposes, and preparing an authority list and research guide/finding aid.

Other future phases of the project/recommendations are the following: 1) conduct a community archiving workshop for the unprocessed photographs in the collection; 2) digitize the processed photographs; and 3) do further studies on the collection for publication (as journal article/book/conferences).
Special Problem
Keywords: Archives -- Processing; Archives -- Collection management